Removing the abyss between conservation science and policy decisions in Brazil - Azevedo-Santos, Valter M. [UNESP]; Fearnside, Philip M.; Oliveira, Caroline S. [UNESP]; Padial, Andre A.; Pelicice, Fernando M.; Lima, Dilermando P.; Simberloff, Daniel; Lovejoy, Thomas E.; Magalhaes, Andre L. B.; Orsi, Mario L.; Agostinho, Angelo A.; Esteves, Francisco A.; et al. (Springer, 2017)
The executive and legislative branches of Brazilian government have either proposed or taken a variety of initiatives that threaten biodiversity and ecosystems. Opposition by the scientific community has largely been ignored by decision-makers. In this short essay, we present recent examples of harmful policies that have great potential to erode biodiversity, and we suggest ways to communicate scientific knowledge to decision- makers. If the current gap between conservation science and policies is not filled, the country will threaten the maintenance of its natural capital and, consequently, the sustainability of essential societal activities in the long term.
Keywords: Environmental laws; Scientific advice; Forest Code; Biodiversity; Translational scientists; Environmental impacts; Neotropical biodiversity